EKSISTENSI TRADISI KAJIAN KITAB KUNING DALAM LINGKUP PERUBAHAN SOSIAL (STUDI KASUS DI PESANTREN DARUN NAHDHAH, DAREL HIKMAH, DAN BABUSSALAM) - Amrizal Amrizal (Sosial Budaya, 2016)
This study wants to find answers about how the existence of stsudy of the yellow book (kitab kuning) at pesantren Darun Nahdhah, Darel Hikmah, and Babussalam within the scope of social change. In general, the three pesantren have responded positively to social change, to make changes and adjustments to the education system, including in order to maintain the tradition of the study of the yellow book. In other words, the identity of pesantren with yellow book still attached at their respective schools. However, its existence is different. Among them, there were made studies of yellow book as co curriculer, together with other curriculum, then there is also making it only limited additional or extra curricular activities.